2015
DOI: 10.1073/pnas.1504822112
|View full text |Cite
|
Sign up to set email alerts
|

The disordered P granule protein LAF-1 drives phase separation into droplets with tunable viscosity and dynamics

Abstract: P granules and other RNA/protein bodies are membrane-less organelles that may assemble by intracellular phase separation, similar to the condensation of water vapor into droplets. However, the molecular driving forces and the nature of the condensed phases remain poorly understood. Here, we show that the Caenorhabditis elegans protein LAF-1, a DDX3 RNA helicase found in P granules, phase separates into P granule-like droplets in vitro. We adapt a microrheology technique to precisely measure the viscoelasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

69
1,357
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,152 publications
(1,433 citation statements)
references
References 42 publications
(54 reference statements)
69
1,357
6
1
Order By: Relevance
“…Intracellular LLPS and the resulting functional membrane‐less organelles, which biophysically can be described as gels or polyelectrolyte brushes, are emerging concepts in cell biology, which are now implicated in manifold cellular functions and applications (Li et al , 2012; Aumiller et al , 2014; Elbaum‐Garfinkle et al , 2015; Jiang et al , 2015; Aguzzi & Altmeyer, 2016; Mitrea et al , 2016; Schmidt & Görlich, 2016; Schmidt & Rohatgi, 2016). For research in neurodegenerative diseases, in particular, the function and misfunction of LLPS by involved proteins—such as tau, FUS, TDP43, hnRNPA1, C9orf72 dipeptide repeats—introduces a novel exciting concept that may provide a common underlying mechanism in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular LLPS and the resulting functional membrane‐less organelles, which biophysically can be described as gels or polyelectrolyte brushes, are emerging concepts in cell biology, which are now implicated in manifold cellular functions and applications (Li et al , 2012; Aumiller et al , 2014; Elbaum‐Garfinkle et al , 2015; Jiang et al , 2015; Aguzzi & Altmeyer, 2016; Mitrea et al , 2016; Schmidt & Görlich, 2016; Schmidt & Rohatgi, 2016). For research in neurodegenerative diseases, in particular, the function and misfunction of LLPS by involved proteins—such as tau, FUS, TDP43, hnRNPA1, C9orf72 dipeptide repeats—introduces a novel exciting concept that may provide a common underlying mechanism in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many nucleolar proteins, including FIB-1 and DAO-5, contain intrinsically disordered domains that are thought to promote assembly of RNA/protein droplets (2,5,8). To determine whether self-interactions between nucleolar components are sufficient for droplet assembly, we purified recombinant FIB-1 and examined its behavior in vitro.…”
Section: In Vitro Phase Separationmentioning
confidence: 99%
“…The mechanisms by which such structures form and stably persist are not well understood. However, recent evidence suggests that these membraneless organelles, such as P granules (1,2), nucleoli (3), and stress granules (4), are liquid-phase droplets that may assemble by intracellular phase separation (5,6). This concept is supported by work on synthetic systems, including repetitive protein domains that form droplets in vitro and in the cytoplasm (7) and intrinsically disordered protein domains that show signatures of liquid-liquid phase separation when expressed in the cell nucleus (8).…”
mentioning
confidence: 99%
“…For these materials, which are often termed "membraneless organelles," the quantity of material, as well as the need to extract such cellular granules from their native environment prevent the application of the types of large-scale SAOS measurements described thus far. However, Elbaum-Garfinkle et al, recently reported the use of microrheology techniques to coacervate-like materials formed as a result of the self-interaction of LAF-1, a DDX3 RNA helicase found in the P granules of Caenorhabditis elegans [190]. Here, confocal fluorescence microscopy was used in conjunction with particle tracking methodologies to measure the viscosity of coacervate-like droplets of LAF-1 both with and without RNA.…”
Section: Linear Viscoelasticity In Vitro and In Vivomentioning
confidence: 99%